Budidaya Jamur Tiram dan Olahannya untuk Kemandirian Masyarakat Desa - Zulfarina Zulfarina; Evi Suryawati; Yustina Yustina; Riki Apriyandi Putra; Hendra Taufik (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
University of Riau with the fostered village program was conducted technology transfer activities on the cultivation of oyster mushrooms in the engagement. The purpose of engagement was to empower the community by cultivating oyster mushrooms and processing oyster mushrooms into products so that they could improve the welfare of Seko Lubuk Tigo village, Lirik District, Indragiri Hulu Regency, Riau Province. The methods used in this activity were: Workshop about The Cultivation of Oyster Mushrooms and Its Processed Products; Discussion of Various Problems and Solutions; Business Management and Product Marketing; Simulation and Evaluation. This Community Service is conducted from June to October 2019. The activity was carried out by involving community service program students of University of Riau as facilitators. The evaluation results of this activity indicated that the cultivation of oyster mushrooms and their preparations had a positive impact on the local community. The community was very responsive to this activity. The prospect of the oyster mushroom market still has considerable opportunities. The output of this activity was the community has been able to do oyster mushroom cultivation and processing. It also produced a reference book about the cultivation of oyster mushrooms.Keywords: baglog; cultivation; oyster mushroom; oyster mushroom’s products.